Protocol for assessing bacterial wilt resistance in greenhouse and field conditions. International cooperators’ guide - Mihovilovich, E.; López, C.; Gutarra, L.; Lindqvist-Kreuze, H.; Aley, P.; Priou, S.; Bonierbale, Merideth W. (International Potato Center, 2017)
This protocol is an updated version of “Assessing potato clone field resistance to bacterial wilt” issued in The International Cooperators’ Guide (CIP 2007). The first edition of the protocol presented a standard procedure for field assessment of resistance to bacterial wilt for documenting levels of resistance of advanced potato germplasm. This second edition has included a standardized procedure for greenhouse screening of potato seedlings for bacterial wilt resistance useful for perform genetic studies, parental selection or identification of new sources of resistance in accessions of wild species propagated or maintained as true seed